Analysis of the U L3-edge X-ray absorption spectra in UO2 using molecular dynamics simulations. (January 2017) - Bocharov, Dmitry; Chollet, Melanie; Krack, Matthias; Bertsch, Johannes; Grolimund, Daniel; Martin, Matthias; Kuzmin, Alexei; Purans, Juris; Kotomin, Eugene
Abstract: Uranium L3 -edge X-ray absorption spectroscopy was used to study the atomic structure of uranium dioxide (UO2 ). The extended X-ray absorption fine structure (EXAFS) was interpreted within the ab initio multiple-scattering approach combined with classical molecular dynamics to account for thermal disorder effects. Nine force-field models were validated, and the role of multiple-scattering contributions was evaluated.